2022
DOI: 10.11113/ijbes.v9.n2.901
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Fire Safety Management in School Facilities

Abstract: Schools are high-risk type of facilities in fire emergencies. This requires the implementation of safety measures, which comprise administrative and operational efforts to mitigate the occurrence of fire accidents. The review of literature indicated the lack of practical approaches that can be easily adopted for safety management in school facilities. This paper presents the development and implementation of a generic framework for fire safety management in school facilities. A literature review in the domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…A focused review of the literature, in the past ten years, on fire risk assessment in the built environment has identified several studies that reported on the assessment of fire safety conditions in various types of buildings. Fire risk assessment were carried out to the provision and keep of fire protection systems in schools (Baldassarra, 2015;Han, 2020;Hassanain et al, 2022a), office workplace (Nimlyat et al, 2017;Li et al, 2018;Hassanain et al 2022b), education facilities (Ebenehi et al, 2017;Salaheldin et al, 2021), residential buildings (Xin and Huang, 2013;Leung and Chow, 2016;Hamida and Hassanain, 2019), student housing facilities (Agyekum et al, 2016;Hassanain et al, 2018) and health care facilities (Ebekozien et al, 2020;Jaafar et al, 2021;Salim et al, 2021). Yet, the literature lacked studies that focus on community centers type of facilities.…”
Section: Historical Incidents and Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A focused review of the literature, in the past ten years, on fire risk assessment in the built environment has identified several studies that reported on the assessment of fire safety conditions in various types of buildings. Fire risk assessment were carried out to the provision and keep of fire protection systems in schools (Baldassarra, 2015;Han, 2020;Hassanain et al, 2022a), office workplace (Nimlyat et al, 2017;Li et al, 2018;Hassanain et al 2022b), education facilities (Ebenehi et al, 2017;Salaheldin et al, 2021), residential buildings (Xin and Huang, 2013;Leung and Chow, 2016;Hamida and Hassanain, 2019), student housing facilities (Agyekum et al, 2016;Hassanain et al, 2018) and health care facilities (Ebekozien et al, 2020;Jaafar et al, 2021;Salim et al, 2021). Yet, the literature lacked studies that focus on community centers type of facilities.…”
Section: Historical Incidents and Previous Studiesmentioning
confidence: 99%
“…A focused review of the literature, in the past ten years, on fire risk assessment in the built environment has identified several studies that reported on the assessment of fire safety conditions in various types of buildings. Fire risk assessment were carried out to the provision and keep of fire protection systems in schools (Baldassarra, 2015; Han, 2020; Hassanain et al. , 2022a), office workplace (Nimlyat et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Rafindadi et al (2022) used the analytical hierarchy process (AHP) model to identify five sub-factors for fall-related accidents in construction sited. Studies have also categorised the causes of construction site accidents as management factors (Hamid et al 2019;Al Zarooni et al 2022;Birhane et al 2022;Chan et al 2022;Deng et al 2022;Khanh and Kim 2022;Zeng et al 2022) and unsafe job site conditions (Hassanain et al 2022;Rahman et al 2022;Zermane et al 2022). Furthermore, the causes of construction site accidents are classified as worker-related, which are due to the actions of workforce (Bidhendi et al 2022;Dolez et al 2022;Kim and Kang 2022;Koc et al 2022;Liang et al 2022;Rafindadi et al 2022;Wu et al 2022).…”
Section: Accidents In Constructionmentioning
confidence: 99%
“…The availability of several sorts of combustibles, including chemicals used in science labs, flammable paper documents, wooden furniture, and class decorations, is blamed for this. Additionally, there is little enforcement of fire safety precautions in schools (Hassanain et al, 2022). According to data released by the Central Agency for Public Mobilization and Statistics (CAPMAS), there were 51.9 thousand fire accidents in Egypt in 2020 as opposed to 50.6 thousand in 2019, this represents a 2.6% rise in disasters (CAPMAS, 2020).…”
Section: Introductionmentioning
confidence: 99%